Mucocutaneous Manifestations of HIV and the Correlation with WHO Clinical Staging in a Tertiary Hospital in Nigeria - Olumayowa Abimbola Oninla (AIDS Research and Treatment)
Skin diseases are indicators of HIV/AIDS which correlates with WHO clinical stages. In resource limited environment where CD4 count is not readily available, they can be used in assessing HIV patients. The study aims to determine the mucocutaneous manifestations in HIV positive patients and their correlation with WHO clinical stages. A prospective cross-sectional study of mucocutaneous conditions was done among 215 newly diagnosed HIV patients from June 2008 to May 2012 at adult ART clinic, Wesley Guild Hospital Unit, OAU Teaching Hospitals Complex, Ilesha, Osun State, Nigeria. There were 156 dermatoses with oral/oesophageal/vaginal candidiasis (41.1%), PPE (24.4%), dermatophytic infections (8.9%), and herpes zoster (3.8%) as the most common dermatoses. The proportions of dermatoses were 4.5%, 21.8%, 53.2%, and 20.5% in stages 1–4, respectively. A significant relationship (using Pearson’s Chi square with P value <0.05) was obtained between dermatoses and WHO clinical stages. Pearson’s correlation coefficient showed a positive correlation between the number of dermatoses and the WHO clinical stages. Dermatoses can therefore serve as diagnostic and prognostic markers in resource limited settings to initiate HAART in clinical stages 3 and 4.